Development of Ultradeformable Liposomes with Fatty Acids for Enhanced Dermal Rosmarinic Acid Delivery - Subongkot, Thirapit (Pharmaceutics, 2021)
This study aimed to develop ultradeformable liposomes (ULs) with fatty acids, namely, oleic, linoleic, and linolenic acid, to improve the skin penetration of rosmarinic acid. This study also investigated the vesicle-skin interaction and skin penetration pathway of ULs with fatty acids using the co-localization technique of multifluorescently labeled particles. The prepared ULs were characterized in terms of size, surface charge, size distribution, shape, % entrapment efficiency (% EE), and % loading efficiency (% LE). The prepared ULs with fatty acids had an average particle size between 50.37 ± 0.3 and 59.82 ± 17.3 nm with a size distribution within an acceptable range and exhibited a negative surface charge. The average % EE and % LE were 9 and 24.02, respectively. The in vitro skin penetration study found that ULs with oleic acid could significantly increase the skin penetration of rosmarinic acid compared to ULs. According to confocal laser scanning microscopy observations, this study suggested that UL vesicles attach to the skin before releasing the entrapped drug to penetrate the skin. These findings suggested that ULs with oleic acid penetrated the skin via the transfollicular pathway as a major penetration pathway.